Suppression of PD‐L1 release from small extracellular vesicles promotes systemic anti‐tumor immunity by targeting ORAI1 calcium channels - Xi Chen; Jiaqi Li; Ren Zhang; Yao Zhang; Xiaoxuan Wang; Elaine Lai‐Han Leung; Lijuan Ma; Vincent Kam Wai Wong; Liang Liu; Erwin Neher; Haijie Yu (Journal of Extracellular Vesicles, 2022)
Abstract Blockade of immune checkpoints as a strategy of cancer cells to overcome the immune response has received ample attention in cancer research recently. In particular, expression of PD‐L1 by various cancer cells has become a paradigm in this respect. Delivery of PD‐L1 to its site of action occurs either by local diffusion, or else by transport via small extracellular vesicles (sEVs, commonly referred to as exosomes). Many steps of sEVs formation, their packaging with PD‐L1 and their release into the extracellular space have been studied in detail. The likely dependence of release on Ca2+‐signaling, however, has received little attention. This is surprising, since the intracellular Ca2+‐concentration is known as a prominent regulator of many secretory processes. Here, we report on the roles of three Ca2+‐dependent proteins in regulating release of PD‐L1‐containing sEVs, as well as on the growth of tumors in mouse models. We show that sEVs release in cancer cell lines is Ca2+‐dependent and the knockdown of the gene coding the Ca2+‐channel protein ORAI1 reduces Ca2+‐signals and release of sEVs. Consequently, the T cell response is reinvigorated and tumor progression in mouse models is retarded. Furthermore, analysis of protein expression patterns in samples from human cancer tissue shows that the ORAI1 gene is significantly upregulated. Such upregulation is identified as an unfavorable prognostic factor for survival of patients with non‐small‐cell lung cancer. We show that reduced Ca2+‐signaling after knockdown of ORAI1 gene also compromises the activity of melanophilin and Synaptotagmin‐like protein 2, two proteins, which are important for correct localization of secretory organelles within cancer cells and their transport to sites of exocytosis. Thus, the Ca2+‐channel ORAI1 and Ca2+‐dependent proteins of the secretion pathway emerge as important targets for understanding and manipulating immune checkpoint blockade by PD‐L1.